Pendekatan Empirisme dalam Pertahanan Perbatasan di laut Natuna Utara - Muh. Ikram Nur Ilahi; Achmed Sukendro; M. Adnan Madjid; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research explores an empiricist approach in the context of border defense in the North Natuna Sea, an area rich in strategic natural resources that requires intensive protection to maintain Indonesia's national and economic security. The research method used is a descriptive qualitative approach, with a focus on the analysis of literature studies that include scientific publications, government reports, and policy documents related to the use of field data in the context of defense. The results of this study show that an empirical approach is the main foundation in the formation of Indonesian policies related to the North Natuna Sea, supported by learning from previous conflict experiences such as the cases of Sipadan and Ligitan Islands. By leveraging strong field evidence, Indonesia ensures that every step taken is based on accurate and verified data. This approach not only enhances Indonesia's legal legitimacy in safeguarding its territorial sovereignty, but also provides a solid foundation for maintaining regional stability and national security in strategic areas such as North Natuna.